Microwave-assisted Synthesis of Ceria-zirconia Mixed Metal Oxide Nanoparticles: Characterization and their Antimicrobial Studies - Ramasamy, Tamilselvi; Arunachalam , Thirumoorthi (Chemical and Materials Sciences - Developments and Innovations Vol. 2, 2024)
The main purpose of this study is to synthesise and characterize the Ceria-Zirconia Mixed Metal oxide nanoparticles. Various preparatory techniques are generally used to prepare/synthesise the nanoparticles such as chemical, photochemical, electrochemical and biological methods. In this study, Ceria-Zirconia Nanoparticles with varied molar ratios of 1:1, 0.8:0.2, 0.6:0.4, 0.4:0.6, and 0.2:0.8 labelled as CZAA-0, CZAA-1, CZAA-2, CZAA-3, and CZAA-4 were prepared utilising Cerium nitrate, Zirconium nitrate, and Ascorbic acid as a promoter. X-ray diffraction, Scanning Electron Microscopy, Ultraviolet-Visible, Raman, and Fourier Transform Infrared Spectra were used to characterise the nanoparticles created. The average crystallite size of synthesized CZAA nanoparticles is 67.29 nm. CZAA NPs were tested for antibacterial activity against Escherichia coli, Klebsiella pneumonia, Staphylococcus aureus, and Enterococcus faecalis bacterial strains, as well as Aspergillus niger, Penicillium, and Candida albicans fungal strains using the well diffusion method. They were shown to be highly anti-functional to all pathogenic strains tested.